Foreign language anxiety in online learning environments: Strategies and implications - Narges Saffari; Mansour Amini; Sze Seau Lee; Maryam Alipour; Bita Naghmeh Abbaspour (Journal of Research, Policy & Practice of Teachers & Teacher Education)
The COVID-19 pandemic exacerbated some anxiety among students, particularly in the realm of higher education where remote learning has become the norm. Despite the escalating prevalence of anxiety among students in the context of online language education, there is a notable absence of comprehensive strategies tailored to effectively mitigate foreign language anxiety (FLA) and support learners, necessitating research to identify evidence-based approaches to address FLA and foster a positive learning environment. This paper reviews the influence of anxiety on language learners, with a focus on the challenges posed by online language education. It explores the multifaceted nature of FLA and its implications for language learning outcomes. The study proposes practical strategies to alleviate anxiety among language learners. These strategies include implementing cooperative learning activities, providing constructive feedback, creating a positive learning atmosphere, addressing individual student needs, giving clear instructions, and establishing a continuous support system. Insights from contemporary research highlight the effectiveness of these approaches in reducing anxiety and fostering a more positive and effective learning environment. Furthermore, the paper discusses the Foreign Language Classroom Anxiety Scale (FLCAS) as a valuable tool for identifying and measuring FLA in online language learning settings. It emphasizes the importance of the psychometric characteristics of FLCAS and its implications for language educators. Finally, by raising awareness of the impact of anxiety on language learning outcomes, and embracing a holistic approach that considers individual, socio-cultural, economic, and technological factors, this paper may provide valuable insights for educators, policymakers, and researchers.